2014
DOI: 10.1136/gutjnl-2014-306834
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of activation of mouse and human enteroendocrine cells by nutrients

Abstract: ObjectiveInhibition of food intake and glucose homeostasis are both promoted when nutrients stimulate enteroendocrine cells (EEC) to release gut hormones. Several specific nutrient receptors may be located on EEC that respond to dietary sugars, amino acids and fatty acids. Bypass surgery for obesity and type II diabetes works by shunting nutrients to the distal gut, where it increases activation of nutrient receptors and mediator release, but cellular mechanisms of activation are largely unknown. We determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
126
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(136 citation statements)
references
References 24 publications
7
126
1
2
Order By: Relevance
“…Infusion of the other single tastants did not modulate feelings of satiety or of food intake. Plasma concentrations of gastrointestinal peptides that are generally considered to play a role in the control of food Several studies reported previously on the expression of taste receptor type 1, taste receptor type 2, and other taste signaling proteins in several parts of the small and large intestine (7,8,16). Activation of these taste receptors, expressed on enteroendocrine cells, may trigger release of several gastrointestinal peptides, including cholecystokinin, GLP-1, and PYY.…”
Section: Gastrointestinal Peptidesmentioning
confidence: 98%
“…Infusion of the other single tastants did not modulate feelings of satiety or of food intake. Plasma concentrations of gastrointestinal peptides that are generally considered to play a role in the control of food Several studies reported previously on the expression of taste receptor type 1, taste receptor type 2, and other taste signaling proteins in several parts of the small and large intestine (7,8,16). Activation of these taste receptors, expressed on enteroendocrine cells, may trigger release of several gastrointestinal peptides, including cholecystokinin, GLP-1, and PYY.…”
Section: Gastrointestinal Peptidesmentioning
confidence: 98%
“…The threshold values for humans refer to the lowest concentration tested following the ascending forced choice triangle test method (Newman & Keast (331) ), which resulted in significant (P < 0·05) detection (E Roura, unpublished results). Pig: tongue (31,334,335) ; stomach, jejunum (51) Human: spermatozoa, testis (336) ; stomach (337) ; liver, HuCCT1 cells (338) ; pancreatic Min6 cells, H9C2 cells and HeLa cells (339) ; tongue fungiform papillae (340) ; adrenal, brain, breast, colon, heart, kidney, lung, ovary, skeletal muscle, testis, thyroid (341) ; stomach antrum, duodenum, proximal jejunum, mid-jejunum, colon, rectum (342) ; pancreas, liver (343) ; intestinal endocrine cells (344) ; GLP-1-producing cells (345) Other: evolutionary analysis (pig) (45) ; sequencing, cloning, cell reporter system (pig) (4,48) TAS1R2…”
Section: Highmentioning
confidence: 99%
“…Sweet 84/76 Carbohydrates (314) , for example: sucrose, saccharin, dulcin and acesulfame-K (346) ; aspartame, cyclamate (347) Pig: tongue (31,334,335) ; small intestine (348) Human: stomach (337) ; duodenum, NCI-H716 cells and GLP-1-producing cells (345) ; liver, HuCCT1 cells (338) ; duodenum, jejunum (349) ; HeLa cells, DU145 cells (350) ; bladder urothelium (351) ; skeletal muscle (341) ; duodenum, jejunum (342) ; tongue (352) Other: evolutionary analysis (pig) (45)…”
Section: Highmentioning
confidence: 99%
“…Specific nutrient receptors in EECs are associated with distinct signaling pathways and lead to the release of a variety of mediators. For example, the protein breakdown product receptor GPR93 and the short-chain fatty-acid receptor FFAR2 are highly expressed in EECs of human and mouse large intestine [Symonds et al 2015]. Upon nutrient activation, the release of neuroactive molecules such as 5-HT and PYY is also differentially modulated [Symonds et al 2015].…”
Section: Intestinal Epithelial Layermentioning
confidence: 99%
“…Among them, enteroendocrine cells (EECs), located at the base of intestinal crypts, transduce mechanic and chemical signals from the intestinal lumen to neighbor cells and the local neuronal network in a paracrine/endocrine fashion [Crowell, 2004;Symonds et al 2015]. Specific nutrient receptors in EECs are associated with distinct signaling pathways and lead to the release of a variety of mediators.…”
Section: Intestinal Epithelial Layermentioning
confidence: 99%